An Experimental Study on Rate Sensitivity of J-Integral and its Evaluation by Small Punch Test for TRIP Steel - Leishi SHI; Takeshi IWAMOTO; Shinya HASHIMOTO (Engineering Transactions, 2014)
Recently, much attention has been paid to TRIP steel since it indicates both high ductility and strength by strain induced martensitic transformation. This transformation allows TRIP steel to offer larger energy absorption than other steel at the same strength level. Therefore, it is expected to be applied to automobiles as security components that absorb energy upon collision. To produce the best performance of TRIP steel, the J-integral of TRIP steel should be investigated with respect to a various deformation rates for an evaluation of energy absorption. In the present study, the three point bending (3B) test is conducted for investigating the J- integral until the crack growth of TRIP steel. Then, in order to determine the energy absorption characteristic by the J-integral value at various locations in the components of TRIP steel, the size of the specimen should be very small. Thus, an SP test is introduced and conducted by using the newly established apparatus based on the SHPB method. By using the result of the SP test in conjunction with the result of a 3B test, the evaluation of the J-integral of TRIP steel subject to various deflection rates is attempted. The correlation between the J-integral and the equivalent fracture strain of the SP test for TRIP steel is challenged to be redefined.